Use of a composite electrode modified with magnetic particles for electroanalysis of azo dye removed from dyed hair strands - Corrêa, Gláucia Tinoco [UNESP] (2016)
The analysis of dyes in hair samples can provide useful information for forensic purposes. The present work describes a novel method for the extraction of dye from a hair sample and its determination using a composite electrode to pre-concentrate carboxyl-functionalyzed magnetic nanoparticles (CFMP) employed to collect the dye in solution, hence increasing the sensitivity of the analysis. The Basic Brown 16 dye, which is widely used in temporary hair dying, was chosen as a model compound. After 15 s of reaction between 1.5 × 10− 5 mol L− 1 of dye and 0.1 mg mL− 1 of carboxyl-functionalyzed magnetic nanoparticles in phosphate buffer electrolyte at pH 7.0, the derivative dye was collected during 40 s at the graphite-epoxy composite electrode and then transferred to a new solution of phosphate buffer at pH 7.0. The dye presented a peak current at a potential of 0.42 V that was almost 400 times higher than without the preconcentration step, suggesting that the dye was pre-accumulated due to strong magnetic interaction with the composite electrode. Under optimized conditions, the analytical curve constructed using square wave voltammetry was linear for BB16 dye concentrations between 1.00 × 10− 7 and 1.00 × 10− 6 mol L− 1. The limits of detection and quantification were 1.01 × 10− 8 and 2.37 × 10− 8 mol L− 1, respectively. The proposed method was successfully applied in the determination of BB16 dye extracted from a dyed hair strand sample by alkaline digestion.